Extracorporeal membrane oxygenation in life-threatening massive pulmonary embolism. (September 2019) - Kjaergaard, Benedict; Kristensen, Jens Hedegaard; Sindby, Jesper Eske; de Neergaard, Susanne; Rasmussen, Bodil Steen
Introduction: In massive pulmonary embolism (PE) with circulatory collapse or with cardiac arrest, treatment can be difficult. Often, the diagnosis is unclear, and the time to treatment is crucial. Our institution has had an out-of-hospital team intended for the treatment of accidental hypothermia with extra corporeal membrane oxygenation (ECMO) since 2004. The team has occasionally been involved in patients suffering massive PE. Methods: We were called to 38 patients with PE, but two were assessed as untreatable. Seventeen were treated with cardiopulmonary resuscitation followed by veno-arterial ECMO. Nineteen were prepared for ECMO with sheaths in the femoral vessels and were intensively observed during diagnosis and treatment. Five of these patients later progressed to ECMO due to cardiac arrest during treatment with thrombolytic medication. Most of the patients were treated with heparin and thrombolytic medication, but if the medications were contraindicated, they were treated with either surgical thrombectomy or only with heparin awaiting spontaneous thrombolysis. Results: Of the 36 patients we intended to treat, 25 (69%) survived one month and 20 survived one year (56%). Of the 22 patients treated with ECMO, 11 survived one month (50%) and 10 survived one year (45%). Discussion: The treatment could have been more uniform. It seems reasonable to build up a PE alert team with ECMO capability to take care of patients with massive PE. Conclusion: The treatment of thrombolytic medications in massive PE is risky, but if the patient is treated or prepared for ECMO, it can be lifesaving.